Diagnosing the Gap in Operational Requirements for the Compliance Management System According to the International Standard ISO 37301:2021 In the General Management of Al-Rasheed Bank / An Applied Research - Dawood, Omar Adel; Lafta, Baydaa Staar (Journal of Ecohumanism, 2024)
The research deals with diagnosing the gap in the 8th requirement (operations) of the Compliance Management System according to the international standard (ISO 37301:2021) at the General Administration of Al-Rashid Bank, which concerns the planning, implementation, and control of processes and procedures designed to address risks and opportunities. The problem of the research lies in the failure to adopt a compliance management system as per the ISO 37301:2021 standard, which has affected the performance of its banking tasks and exposed it to non-compliance risks. Therefore, a compliance management system is required to reduce the likelihood of such risks, which is the main objective of the research. The study compares the current operations of the compliance management system at Al-Rashid Bank with the operational requirements specified in ISO 37301:2021, using audit checklists for this requirement in order to diagnose non-compliance gaps and provide a qualitative analysis of the existing gap. The research relied on percentages and weighted arithmetic means, and found that the application and documentation of the operational requirement at the bank were insufficient, with a gap percentage of 45.84%. Thus, addressing these gaps requires improvements and system reviews to reduce them.